Synthesis, characterization and photocatalytic studies of CdS incorporated titanosilicate for hydrogen generation - Ng, Yew Choo (2009)
This study relates to a development of heterogeneous solid catalyst, Engelhard titanosilicate (ETS-10) supported cadmium sulfide (CdS) for water splitting reaction to generate hydrogen under visible light irradiation. Highly crystalline truncated bipyramid shape of ETS-10 was successfully synthesized with the molar composition of TiO2:3.75SiO2:1.5NaOH:0.54KF:21.25H2O at 220oC for 52 hours. The as-synthesized CdS crystallized at the size of approximately 8 nm in the cubic structure with the lattice constant a=0.5818 nm and reflection peaks of (111), (220) and (331) lattice planes. The effect of the synthesis route of CdS, the effect of percentage loading of CdS and reusability of the catalysts towards water splitting were also reported. The conduction edge of the photocatalyst was found to be more negative than H+/H2 redox potential. The highly crystalline phases of photocatalyst were able to prevent a charge recombination leading to enhancement in the hydrogen production yield. The existence of co-catalyst (ETS-10) in the catalytic system induces reduction of water and increases the efficiency of charge separation. The hybrid photocatalyst was found to be more stable and do not undergo photo-corrosion. CdS derived from in-situ sulphur reduction method (CdS-IS) performed better than CdS derived from reverse micelle method (CdS-RM). For 0.1 g of catalyst, the average rate of reaction for the first 5 hours was found to be 68.69 µmol/hr and 49.05 µmol/hr for CdS-IS and CdS-RM respectively. Besides, the results showed that the higher the percentage of CdS loaded on ETS-10, the higher amount of hydrogen gas liberated. The reusability of the photocatalysts was demonstrated in three cycles and the hydrogen gas evolved slightly decreased with the number of the reusability.